Outcomes of neuropsychiatric events in systemic lupus erythematosus based on clinical phenotypes; prospective data from the Leiden NP SLE cohort. (April 2017) - Magro-Checa, C; Beaart-van de Voorde, L J J; Middelkoop, H A M; Dane, M L; van der Wee, N J; van Buchem, M A; Huizinga, T W J; Steup-Beekman, G M
Objective: The objective of this study was to assess whether clinical and patient's reported outcomes are associated with a different pathophysiological origin of neuropsychiatric events presenting in systemic lupus erythematosus. Methods: A total of 232 neuropsychiatric events presenting in 131 systemic lupus erythematosus patients were included. Neuropsychiatric systemic lupus erythematosus diagnosis was established per event by multidisciplinary evaluation. All neuropsychiatric events were divided according to a suspected underlying pathophysiological process into one of the following: non-neuropsychiatric systemic lupus erythematosus related, inflammatory and ischaemic neuropsychiatric systemic lupus erythematosus. The clinical outcome of all neuropsychiatric events was determined by a physician-completed four-point Likert scale. Health-related quality of life was measured with the subscales of the patient-generated Short Form 36 (SF-36) health survey questionnaire. The change between scores at paired visits of all domain scores, mental component summary (SF-36 MCS) and physical component summary (SF-36 PCS) scores were retrospectively calculated and used as patient-reported outcome. The association among these outcomes and the different origin of neuropsychiatric events was obtained using multiple logistic regression analysis. Results: The clinical status of 26.8% non-neuropsychiatric systemic lupus erythematosus events, 15.8% ischaemic neuropsychiatric systemic lupus erythematosus and 51.6% inflammatory neuropsychiatric systemic lupus erythematosus improved after re-assessment. Almost all SF-36 domains had a positive change at re-assessment in all groups independently of the origin of neuropsychiatric events. Neuropsychiatric systemic lupus erythematosus ( B  = 0.502; p  < 0.001) and especially inflammatory neuropsychiatric systemic lupus erythematosus ( B  = 0.827; p  < 0.001) had better clinical outcome, with change in disease activity being the only important predictor. The change in SF-36 MCS was also independently associated with neuropsychiatric systemic lupus erythematosus ( B  = 5.783; p  < 0.05) and inflammatory neuropsychiatric systemic lupus erythematosus ( B  = 11.133; p  < 0.001). Disease duration and change in disease activity were the only predictors in both cases. The change in SF-36 PCS was only negatively associated with age. Conclusion: Inflammatory neuropsychiatric systemic lupus erythematosus events have better clinical outcome and meaningful improvement in SF-36 MCS than ischaemic neuropsychiatric systemic lupus erythematosus or non-neuropsychiatric systemic lupus erythematosus.